Fermatean Picture Fuzzy Continuity in Fermatean Picture Fuzzy Topological Spaces - Chitra, V.; Maheswari, B.; Jafari, S. (Communications in Mathematics and Applications, 2025)
The purpose of this paper is to define a new Picture fuzzy continuous mapping in Fermatean picture fuzzy topological spaces and investigate its fundamental properties. In addition, we explore a key topological concept FPF-\(β\) connectedness within the framework of Fermatean picture fuzzy topology.
Keywords: Fermatean picture fuzzy set; Fermatean picture fuzzy topological spaces; Fermatean picture fuzzy continuous mapping; FPF-β connectedness